The Role Of Law In Providing Decent Work For Citizens To Support The National Long-Term Development Plan 2025-2045 - Wijaya, Andri (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study discusses the role of law in fulfilling decent work for citizens to support the National Long-Term Development Plan (RPJPN) 2025-2045. The government always strives to provide and create decent jobs for its citizens, but unfortunately, the number of jobs is insufficient to meet the large number of prospective Indonesian workers. One reality on the ground is the widespread layoffs by companies for various reasons. As a developing country, layoffs have had various negative impacts on ongoing development. The high unemployment resulting from layoffs certainly has a systemic impact on the economy and development in Indonesia. The RPJPN 2025–2045 serves as the legal basis and primary guideline for all development actors—both government and non-government—in realizing Indonesia's grand vision by 2045, known as the "Vision of Golden Indonesia 2045." In the Vision of Golden Indonesia 2045, the phrase "sustainable" is written, which means that Indonesia has a dream of implementing continuous development without stopping with the support of various sectors. The labor sector plays an important role in realizing this sustainable development, but this sustainable development will experience obstacles if there is a lot of unemployment due to layoffs. This study employs a normative legal research method. The results of the study indicate that The Golden Indonesia 2045 Vision and the 2025–2045 RPJPN directly address the issue of layoffs through inclusive and sustainable economic development, improving human resource quality, digital and industrial transformation, and adaptive employment policies.